The Representation of Satirical Cartoon Themes In Commercial Advertising (Journal of the College of Basic Education, 2026)
Contemporary graphic design is multifaceted and diverse due to its continuous development and modernization. It provides graphic designers with numerous means to express their ideas, varying according to the design's subject matter. These means include text, colors, and illustrations. Satirical cartoons are a promotional tool for various commercial advertisements, becoming more memorable and appealing to the public. They are similar in their ability to convey philosophical and thematic themes. McDonald's has used them to promote its services, making them part of its visual identity that distinguishes it from other advertising agencies. Therefore, the researcher posed the following question, representing the research problem: Do satirical cartoon themes have representations in advertising promotion? Commercial?The researcher then moved to the theoretical framework, which included the following sections: Section One: (Satirical Cartoons: Origins and Concept), comprising three points; Section Two: (Satirical Cartoons in Typographic Design), comprising four points; and the final chapter, which included the researcher's findings after analyzing the models. Following this, the researcher offered several recommendations and suggestions to further this study. The research concludes with a list of sources.